Electromagnetic Transient Simulations for Undergraduate Students Using a Low Complexity Numeric Routine - Monzani, R. C.; Prado, A. J. [UNESP]; Kurokawa, S. [UNESP]; Bovolato, L. F. [UNESP]; Pissolato Filho, Jose; IEEE (Ieee, 2010)
This paper presents a mathematical model to simulate and analyze electromagnetic transients in transmission lines using a mono-phase representation of these lines comparing results models with and without frequency influence in longitudinal parameters. For this, pi circuits and state variables are used for composing a linear system that is solved through iterative numeric routines. This routine is applied to MatLab (TM) program. Using a simpler model than EMTP, undergraduate students of Electrical Engineering, Computing, Mathematic and other courses can apply the propagation wave theory and simulate the electromagnetic transient propagations in transmission line representation, awaking these students for power system analyses.
Keywords: Electromagnetic transient; EMTP; mathematical model; simulation; transmission lines